Estudio toxicológico y fitoquímico de Pernettia coriacea Klotzsch - Sáenz, J. A. (1967)
On the summits and high slopes of the mountains of Costa Rica grow several species of shrubby heath-like plants, collectively known as "arrayán". Toxicological study of the fruit of truee of the most characteristic species is reported. Those of Vaccinium consanguineum Klotz. and Myrtus oerstedii (Berg) Hemsl. were found to be innocuous. Those of Pernettia coriacea Klotz. were found to be toxico The toxic principle was isolated and tentatively named pernettine. Some physical and chemical characteristics of the substance are reported.